Identification of PBAN-like immunoreactivity in the neuroendocrine system and midgut of Dysdercus cingulatus (Heteroptera: Pyrrhocoridae) - Viswanathan Sarada AJITHA; Damodaran MURALEEDHARAN (European Journal of Entomology, 2001)
Polyclonal antibodies against PBAN were used to map the distribution of PBAN-like antigenic sites in the brain-suboesophageal ganglion (Br-SOG) complex, associated neurohaemal structures, ventral nerve cord ganglia and in the alimentary canal. A pair of lateral neurosecretory cells immunopositive to the antiserum were found in each half of the deutocerebrum. PBAN-like immunoreactivity (PLI) was also noticed in the tritocerebral region of the brain and in the aorta. Two groups of immunopositive cells of four and two cells respectively, were found in the SOG. Small and weakly immunoreactive neurons were identified in the prothoracic ganglion, whereas in the pterothoracic ganglion a pair of cells reacted positively to the antibody. Immunoreactive cells were also identified in the corpora cardiaca. Some of the epithelial endocrine cells of the midgut also showed immunoreactivity to PBAN antiserum.